Insulating and sheathing materials of electric cables. Methods of test specific to polyethylene and polypropylene compounds. Resistance to environmental stress cracking. Wrapping test after thermal ageing in air. Measurement of the melt flow index. Carbon black and/or mineral content measurement in PE Part 4-4.1, (15th August 1992) - British Standards Institution,
No abstract available